(untitled) - Shinohara, Miyohei (Tokyo, 1982)
This book introduce about industrial growth and industrial policy. Changes in trade structure. Dynamic patterns in growth and cycles.
Keywords: Điều kiện kinh tế,Economic conditions; Nhật Bản; Japan,Japan